Bone metabolism markers in response to three and six sessions of low energy extracorporeal shockwave therapy in individuals with post anterior cruciate ligament reconstruction - Marhasiyah Rahim,; Foong, Kiew Ooi; Tengku Muzaffar Tengku Mohamed Shihabudin,; Chee, Keong Chen (Penerbit Universiti Kebangsaan Malaysia, 2021)
Precise information on the effects of extracorporeal shockwave therapy (ESWT) on biochemical status in humans is still lacking. Hence, this study investigated the effectiveness of three or six sessions of low energy ESWT on serum bone metabolism markers in individuals who have undergone post anterior cruciate ligament (ACL) reconstruction. Participants with ACL injuries were assigned into three groups (n=10 per group), i.e. physiotherapy alone without ESWT (control), three sessions of ESWT combined with physiotherapy (3ESWT), and six sessions of ESWT combined with physiotherapy (6ESWT) groups. Serum bone metabolism markers, i.e. osteocalcin (OCN), human Cross Linked C-telopeptide of Type 1 Collagen (CTX1), calcium, and phosphorus were measured at weeks 0, 2, 9, 12, and 6 months post ACL reconstruction. Serum OCN and CTX1 concentrations within the 3ESWT and 6ESWT groups across the five measurements were not significantly different. However, serum calcium concentrations at weeks 2, 9, and 12 were significantly higher compared to their respective baseline values for all three groups. Shockwave therapy had no significant effect on bone resorption and formation markers postoperatively. Six sessions of shockwave therapy (6ESWT) elicited the highest serum calcium level at week 12 post-operatively among all the groups. More studies are warranted to substantiate these findings.